Antioxidant Properties of Ethanol and Water Extracts of Different Parts of Salvia russellii Bentham Plant - Turkoglu, S.; Celik, S.; Turkoglu, I. (Asian Journal of Chemistry, 2011)
In this study, the antioxidant activity of water and ethanol extracts of Salvia russellii leaves and flowers was evaluated by various antioxidant assay, ABTS' (2,2'-azino-bis-(3-ethylbenzothiazoline-6-sulphonic acid)) radical scavenging capacity, DPPH center dot (2,2-diphenyl-1-picrylhydrazyl) radical scavenging capacity, superoxide anion radical scavenging capacity, hydrogen peroxide scavenging capacity, reducing power and metal chelating activities. Various antioxidant activities were compared to standard antioxidants such as butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT) and alpha-tocopherol. The extracts of Salvia russellii showed strong antioxidant activity. The extracts of Salvia russellii have effective antioxidant assay. This antioxidant property depends on concentration and increasing with increased amount of sample. The results obtained in the present study indicated that Salvia russellii leaves and flowers is a potential source of natural antioxidant.
Keywords: Salvia russellii; Antioxidant activity; In vitro; Leaves and Flowers